Perancangan Sistem Keamanan Berbasis Limit Switch Sensor dan GPS Tracking System Bagi Penyedia Jasa Layanan Pengiriman Barang: Studi Kasus - Roni Zakaria; Yuniaristanto -; Yonatan Ardi Hardono (Performa: Media Ilmiah Teknik Industri, 2011)
Design of security shipment is done by integrating GPS tracking and sensor limit switches to SMS Gateway technology in a single application system. Every movement of delivery vehicles monitored by the system and PT. Pos receive notifications via SMS in accordance with the state of the open door, the vehicle stops and there is no GPS signal.The designstarts fromdesigningthe trackingapplication usingvisual basicinterface06 .The next step is integrating GPS tracking and limit switch sensorwhit tracking application that have made.The application tested by using real shipment case study.